Inductor material, preparation method thereof and inductor

By using insulating coated coarse powder and fine powder grading and inorganic cladding in the inductive material, an interlocking structure and close combination is formed, which solves the cracks and inductance caused by stress during the module packaging process of inductive material. The problem of volume reduction achieves stability and packaging matching under high pressure, significantly improving the reliability of inductor materials.

CN119207931APending Publication Date: 2024-12-27SHENZHEN SUNLORD ELECTRONICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411374156.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

During the module packaging process, existing inductor materials are prone to internal cracks and inductance drop due to shrinkage stress, resulting in the reliability risk of power supply modules. Existing improved methods such as expansion coefficient matching and magnet strength increase fail to effectively solve the risk of cracking.

Method used

Using 96.5 to 98.6 wt% composite material and 1.4 to 3.5 wt% resin, the particle occlusion interface is formed by insulating coated coarse powder and fine powder grade, and combined with inorganic cladding layer and resin to form an interlocking structure and close bonding. , improve the thermal expansion coefficient of the material and the strength of the magnet, and ensure the insulation ability and compressive resistance under high pressure.

Benefits of technology

The stability and packaging matching of inductor materials under high pressure are achieved, the volume resistivity is above 1*107Ω·m, and the inductance change rate after packaging is less than 5%, which significantly reduces the risk of insulation failure caused by packaging stress, and is suitable for modules. Package inductors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119207931A_ABST
    Figure CN119207931A_ABST
Patent Text Reader

Abstract

The invention discloses an inductor material, a preparation method thereof and an inductor. The inductance material comprises 96.5 wt% to 98.6 wt% of a composite material and 1.4 wt% to 3.5 wt% of resin. The composite material comprises 50-80 wt% of insulation-coated coarse powder, 19.9-49.2 wt% of insulation-coated fine powder and 0.1-0.8 wt% of a coupling agent, the insulation-coated coarse powder comprises a first magnetic material and a first inorganic coating layer coating the first magnetic material, the surface appearance of the insulation-coated coarse powder is spherical, the sphericity degree of the insulation-coated coarse powder is 0.75-0.90, and the insulation-coated fine powder comprises a second magnetic material and a second inorganic coating layer coating the first magnetic material. The insulation-coated fine powder comprises a second magnetic material and a second inorganic coating layer coating the second magnetic material, the surface appearance of the insulation-coated fine powder is an irregular sphere-like shape, and the sphericity degree of the insulation-coated fine powder is 0.05-0.3. The inductance material has excellent pressure resistance and packaging matching performance, the volume resistivity of the material is 1 * 10 < 7 > omega.m or above under 900 MPa, meanwhile, the inductance change rate is smaller than 5% after the inductance material is packaged into a module, and the inductance material can be used for preparing an inductor suitable for module packaging current and has high application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electronic components, and in particular to an inductor material and a preparation method thereof, and an inductor. Background Art

[0002] With the widespread application of power packaging modules, the corresponding inductors have put forward the requirement of matching the packaging process to meet the module packaging. Since the existing inductors have formed a solid structure, the shrinkage stress generated during the module packaging process may easily cause internal cracks in the inductor and the risk of reduced inductance, which will create reliability risks for the integrated packaged power modules.

[0003] In order to obtain an inductor material that does not crack during packaging, materials that match the expansion coefficient, increase the magnetic strength, or reduce the characteristic changes caused by the material's stress resistance are generally used. However, the cracking caused by the small thermal expansion coefficient of the inductor material can be improved by matching the thermal expansion coefficient. After packaging, stress is easily generated, causing characteristic changes. By increasing the magnetic strength, the packaging stress on the material does not change because the stress it is subjected to does not change. By improving the material's ability to resist stress performance changes, the impact of stress on the electrical properties of the inductor can be reduced, but the risk of mechanical characteristics such as cracking is not reduced.

[0004] Therefore, how to improve the existing inductor material system to achieve its packaging inside the power module without reliability risk is the current technical difficulty.

[0005] It should be noted that the information disclosed in the above background technology section is only used for understanding the background of the present application, and therefore may include information that does not constitute prior art known to ordinary technicians in the field. Summary of the invention

[0006] The invention provides an inductor material, a preparation method thereof and an inductor.

[0007] The present invention adopts the following technical solution:

[0008] In a first aspect, an inductive material is provided, which includes 96.5-98.6wt% of a composite material and 1.4-3.5wt% of a resin; the composite material includes 50-80wt% of an insulation-coated coarse powder, 19.9-49.2wt% of an insulation-coated fine powder and 0.1-0.8wt% of a coupling agent, wherein the insulation-coated coarse powder includes a first magnetic material and a first inorganic coating layer coating the first magnetic material, the surface morphology of the insulation-coated coarse powder is spherical, and the sphericity thereof is 0.75-0.90, the insulation-coated fine powder includes a second magnetic material and a second inorganic coating layer coating the second magnetic material, the surface morphology of the insulation-coated fine powder is an irregular spherical shape, and the sphericity thereof is 0.05-0.3.

[0009] In a second aspect, a method for preparing the inductive material according to the first aspect is provided, which comprises the following steps:

[0010] (1) Preparing insulation-coated coarse powder: performing insulation coating on the first magnetic material to form a first inorganic coating layer to obtain insulation-coated coarse powder;

[0011] (2) preparing insulation-coated fine powder: performing insulation coating on the second magnetic material to form a second inorganic coating layer to obtain insulation-coated fine powder;

[0012] (3) Grading: 50-80 wt% of the insulation coated coarse powder, 19.9-49.2 wt% of the insulation coated fine powder and 0.1-0.8 wt% of the coupling agent are diluted into a slurry, and then wet ball milling is performed, spray drying is performed, and grading is performed to obtain a composite material with a particle size of 50-150 μm;

[0013] (4) Granulation: 96.5-98.6 wt% of the composite material and 1.4-3.5 wt% of the resin are heated and mixed, then cooled and crushed, and the inductor material with a particle size of 40-120 μm is selected.

[0014] In a third aspect, an inductor is provided, which includes a magnet, a coil and a pin, wherein the coil is located in the magnet, the pin is connected to the coil and protrudes from the magnet, and the magnet includes the inductor material described in the first aspect.

[0015] Compared with the prior art, the beneficial effects of the present invention include the following:

[0016] 1. The present invention adopts spherical insulation coated coarse powder and irregular shaped insulation coated fine powder grading to form a particle bite interface, and an interlocking structure is formed between the irregular spherical insulation coated fine powder particles. At least part of the spherical insulation coated coarse powder particles are confined in the interlocking structure. While the spherical particles provide a uniform air gap to maintain a certain thermal expansion ratio, the interlocking structure of the irregular spherical material forms a higher magnetic strength (elastic modulus greater than 50GPa), so that the material still has a more suitable thermal expansion coefficient (thermal expansion coefficient greater than 35ppm / ℃) at a higher strength.

[0017] 2. The coating layer provides better insulation ability through the control of the composite coating structure formed by composite inorganic coating. At the same time, the coating layer has good compressive resistance, which ensures that the insulation layer is not broken when the material is prepared under high pressure, providing better insulation ability, and will not cause insulation failure due to the stress of the packaging material during inductor packaging. At the same time, the coating layer has amine compounds, and the resin and powder are tightly combined, which further improves the strength of the matrix.

[0018] 3. In some technical solutions, through the design of the resin, the resin contains 61-70wt% epoxy resin and 30-39wt% phenolic resin or polyimide. The pressure of the prepared product is relatively small, so that the deformation of the internal coil of the inductor is small, so that the coil will not generate residual stress during the inductor preparation process, and a large internal expansion coefficient will be generated during the hot and cold shock process, which reduces the stress on the internal composite material and coil.

[0019] The inductor material of the present invention can be used to prepare inductors for module packaging, surface mounting, etc. In particular, the inductor of the present invention has excellent pressure resistance and packaging matching. The volume resistivity of the material under 900 MPa is 1*10 7 At the same time, the inductance change rate after being packaged into the module is less than 5%. It is particularly suitable for preparing inductors suitable for module packaging current use and has great application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 3 is a cross-sectional SEM image of the inductor material of Example 2 of the present invention.

[0021] Figure 2 is a schematic cross-sectional view of an inductor according to a specific embodiment of the present invention. DETAILED DESCRIPTION

[0022] The following is a detailed description of the embodiments of the present invention. It should be emphasized that the following description is only exemplary and is not intended to limit the scope and application of the present invention. In the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other.

[0023] A specific embodiment of the present invention provides an inductor material, which includes 96.5-98.6wt% of a composite material and 1.4-3.5wt% of a resin; the composite material includes 50-80wt% of an insulation-coated coarse powder, 19.9-49.2wt% of an insulation-coated fine powder and 0.1-0.8wt% of a coupling agent, wherein the insulation-coated coarse powder includes a first magnetic material and a first inorganic coating layer coating the first magnetic material, the surface morphology of the insulation-coated coarse powder is spherical, and the sphericity thereof is 0.75-0.90, the insulation-coated fine powder includes a second magnetic material and a second inorganic coating layer coating the second magnetic material, the surface morphology of the insulation-coated fine powder is an irregular spherical shape, and the sphericity thereof is 0.05-0.3.

[0024] In a specific embodiment of the present invention, the particle size of the coarse powder is larger than that of the fine powder. Spherical coarse powder and irregularly shaped fine powder are graded to form a particle bite interface. An interlocking structure is formed between the irregular spherical fine powder particles. At least part of the spherical coarse powder particles are confined in the interlocking structure. While the spherical particles provide a uniform air gap to maintain a certain thermal expansion ratio, the interlocking structure of the irregular spherical material forms a higher magnetic strength (elastic modulus greater than 50 GPa), so that the inductor material still has a more suitable thermal expansion coefficient (thermal expansion coefficient greater than 35 ppm / °C) at a higher strength.

[0025] The insulating coating on the surface of the coarse powder and the fine powder provides better insulation ability. At the same time, the coating has good compressive resistance, which ensures that the insulating layer is not broken when the material is used to prepare products under greater pressure, provides better insulation ability, and will not cause insulation failure due to the stress of the packaging material during inductor packaging. At the same time, the composite material includes a coupling agent, and the resin and powder are tightly combined to further improve the strength.

[0026] The above-mentioned inductor material has excellent pressure resistance and packaging matching. Its volume resistivity is 1*10 7 At the same time, the inductance change rate after being packaged into the module is less than 5%. It can be used to prepare inductors suitable for module packaging current use and has great application value.

[0027] In some embodiments, the particle size distribution of the inductive material is in the range of 40 to 120 μm.

[0028] In some embodiments, the coupling agent is an amine compound. By using the amine compound as a coupling agent, the composite material particles and the resin are tightly bonded, further improving the strength.

[0029] In some embodiments, the coupling agent is at least one of aminopropylmethyldiethoxysilane, aminopropylmethyltriethoxysilane, aminopropylmethyldimethoxysilane, and aminopropylmethyltrimethoxysilane.

[0030] In some embodiments, in the insulating coated coarse powder, the first magnetic material is at least one of amorphous powder, nanocrystalline powder, FeSi powder, FeSiAl powder, FeSiCr powder, and FeNi powder, and the particle size distribution is in the range of 6 to 50 μm. The material of the first inorganic coating layer is at least one of aluminum oxide, silicon oxide, titanium oxide, ZnO and P2O5, and the thickness of the first inorganic coating layer is 30 to 100 nm.

[0031] In some embodiments, in the insulating coated fine powder, the second magnetic material is at least one of carbonyl iron powder, amorphous powder, FeSi powder, FeSiAl powder, FeSiCr powder, and FeNi powder, and the particle size distribution is in the range of 1 to 12 μm. The material of the second inorganic coating layer is at least one of aluminum oxide, silicon oxide, titanium oxide, ZnO and P2O5, and the thickness of the second inorganic coating layer is 3 to 10 nm.

[0032] In some embodiments, the resin is at least one of epoxy resin, phenolic resin, acrylic resin, and polyimide.

[0033] In some embodiments, the resin comprises 61-70 wt % of epoxy resin and 30-39 wt % of phenolic resin or polyimide, based on the weight of the resin.

[0034] The specific embodiment of the present invention also provides a method for preparing the inductive material, comprising the following steps:

[0035] (1) Preparing insulating coated coarse powder: insulatingly coating the first magnetic material to form a first inorganic coating layer, thereby obtaining insulating coated coarse powder; in a specific embodiment, the first magnetic material may be coated with multiple layers (e.g., 1-3 layers) to finally form an inorganic composite coating layer of 30 to 100 nm;

[0036] (2) Preparing insulating coated fine powder: insulatingly coating the second magnetic material to form a second inorganic coating layer to obtain insulating coated fine powder; in a specific embodiment, the second magnetic material may be coated with multiple layers (e.g., 1-3 layers) to finally form an inorganic composite coating layer of 3 to 10 nm;

[0037] (3) Grading: 50-80 wt% of the insulation coated coarse powder, 19.9-49.2 wt% of the insulation coated fine powder and 0.1-0.8 wt% of the coupling agent are diluted into a slurry, and then wet ball milling is performed, spray drying is performed, and classification is performed (for example, classification is performed by a classification device) to obtain a composite material with a particle size of 50-150 μm;

[0038] (4) Granulation: 96.5-98.6 wt% of the composite material and 1.4-3.5 wt% of the resin are heated (for example, heated at 50-90° C.), mixed, cooled and crushed, and the inductor material with a particle size of 40-120 μm is selected.

[0039] A specific embodiment of the present invention further provides an inductor, which includes a magnet, a coil and a pin. The coil is located in the magnet. The pin is connected to the coil and protrudes from the magnet. The magnet includes the inductor material.

[0040] In some embodiments, the magnet is formed by pressing the inductive material, and the particle size of the surface particles of the magnet after pressing is in the range of 20 to 140 μm. The particle size of the particles on the surface of the magnet is controlled by pressing using an inductive material with a particle size of 40 to 120 μm. For example, the particle size of the surface particles of the magnet can be controlled to be in the range of 30-80 μm by pressing at a pressure of 900 MPa. By controlling the particle size of the surface particles of the magnet to be in the range of 20 to 140 μm, the filling between the particles can be made tighter and a higher strength can be maintained.

[0041] In some embodiments, the pin protrudes from the magnet by 0.02-0.20 mm to facilitate the packaging material to enter the bottom of the inductor electrode during the packaging process.

[0042] The specific embodiments of the present invention are further described below.

[0043] The coarse powder types and insulating coating layers in the embodiment are shown in Table 1 below:

[0044]

[0045] The types of fine powder and insulating coating layers in the embodiments are shown in Table 2 below:

[0046]

[0047]

[0048] The compositions of the inductor materials in various embodiments and comparative examples are shown in Table 3 below, where % in the table refers to weight percentage by weight:

[0049]

[0050]

[0051]

[0052] Note: In the above Table 3, the coupling agent in Examples 1-3 is propylmethyldiethoxysilane, the coupling agent in Example 4 is aminopropylmethyltriethoxysilane, the coupling agent in Example 5 is aminopropylmethyldimethoxysilane, and the coupling agent in Example 6 is aminopropylmethyltrimethoxysilane.

[0053] The preparation of the inductor materials and inductors of the above-mentioned embodiments and comparative examples includes the following steps:

[0054] 1) Surface treatment of coarse powder: According to Table 1, the coarse powder of each embodiment and comparative example was coated with inorganic insulation.

[0055] 2) Surface treatment of fine powder: According to Table 2, the fine powder of each embodiment and comparative example was coated with inorganic insulation.

[0056] 3) Grading: According to Table 3, each component of the composite material of each embodiment and comparative example was weighed, diluted into slurry by a diluent, and then dispersed by wet ball milling, spray dried, and classified by a classification device. The particle size was controlled to be 50 to 150 μm, and the composite material was obtained after classification;

[0057] 4) Granulation: According to Table 3, the composite materials and resin components of each embodiment and comparative example are heated and mixed at 50-90°C, cooled and crushed, and passed through a screening device to obtain an inductor material with a final particle size controlled at 40-120 μm. Figure 1 , which is a cross-sectional SEM image of the inductor material obtained in Example 2, from which it can be seen that the spherical particles are distributed between the interlocking non-spherical particles, which can improve the strength of the material.

[0058] 5) The inductor materials of each embodiment and comparative example are pressed by a press and a coil to form an inductor blank; wherein the surface particles of the inductor magnet are 20-140 μm, wherein the pins of the coil protrude from the magnet by 0.02-0.20 mm to facilitate the packaging material to enter the bottom of the inductor electrode during the packaging process.

[0059] 6) Curing the inductor body at 160-200° C. for 1-3 hours;

[0060] 7) Spray resin on the surface of the cured inductor blank, and after drying, use laser burning to expose the bottom coil terminal structure;

[0061] 8) Tin the coil terminal surface to obtain a power inductor, such as Figure 2 As shown, it includes a magnet 3, a coil 2 and a pin 1, wherein the coil 2 is located inside the magnet 3, the pin 1 is connected to the coil 2 and protrudes from the magnet 3, and the magnet 3 is formed by pressing the inductive material.

[0062] The inductor material and the inductor of the embodiment of the present invention are subjected to performance tests, wherein:

[0063] The inductor material obtained in step 4) was made into a disc with a diameter of 11 mm and a thickness of 2 mm, and the thermal expansion coefficient of the material was tested using a thermal expansion analyzer; the inductor material obtained in step 4) was made into a strip sample with a length of 30 mm* a width of 4 mm* a height of 3 mm, and the elastic modulus was tested using a universal testing instrument CMT11012; the inductor material obtained in step 4) was made into a disc with a diameter of 5 mm and a thickness of 3 mm, and its resistivity was tested using a high resistance meter 4339B+16008B. The results are shown in Table 4.

[0064] The change of electromagnetic inductance before and after packaging of the power inductor obtained by LCR test step 8) is obtained. The packaging material is Kyocera's EMC material KE-G850S, the packaging pressure is 5MPa, and the size of the power inductor is: length 2.0mm*width 1.6mm*height 1.0mm. The results are detailed in Table 5.

[0065] Table 4: Electromagnetic properties of samples of embodiments and comparative examples

[0066]

[0067]

[0068] As can be seen from Table 4, the elastic modulus of the material obtained in the embodiment is higher, indicating that the deformation of the material is small, the strength is better, the thermal expansion coefficient is similar to the expansion coefficient of the copper wire and chip packaging material, and it is less likely to produce stress and other problems. At the same time, the sample prepared under high pressure has a high resistivity, indicating that the material has good insulation and compressive resistance.

[0069] Table 5: Electromagnetic properties of the 2mm*1.6mm*1.0mm power inductors of the embodiments and comparative examples measured at 1MHz before and after packaging

[0070] serial number Inductance 1@1MHz (μH, before packaging) Inductance 2@1MHz (μH, packaged) Example 1 0.451 0.443 Example 2 0.473 0.466 Example 3 0.480 0.469 Example 4 0.486 0.475 Example 5 0.493 0.477 Example 6 0.472 0.461 Comparative Example 1 0.470 0.443 Comparative Example 2 0.462 0.419 Comparative Example 3 0.461 0.424

[0071] As can be seen from Table 5, in the present invention, the inductance change rate after encapsulation into the module is less than 5% for Examples 1-6, and the prepared inductor solves the risk of performance degradation and internal defects caused by packaging stress in the power packaging module. Comparative Example 1 uses spherical fine powder grading, the material elastic modulus is small, and the thermal expansion coefficient is greatly different from the thermal expansion coefficient of the packaging material (about 40ppm / ℃), the stress formed is large, the inductance changes greatly after packaging, and there is a greater risk of short circuit. Comparative Example 2 uses a coarse powder without grading, the problem is the same as Comparative Example 1, and because the elastic modulus is smaller, the risk of cracking after being stressed increases. Comparative Example 3 only uses epoxy resin for bonding, and the resin cross-linking density is low, resulting in insufficient stress resistance.

[0072] The above content is a further detailed description of the present invention in combination with specific / preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, it can also make several substitutions or modifications to these described embodiments, and these substitutions or modifications should be regarded as belonging to the protection scope of the present invention. In the description of this specification, the description of the reference terms "an embodiment", "some embodiments", "preferred embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in combination with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily target the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In the absence of mutual contradiction, those skilled in the art can combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples. Although the embodiments of the present invention and their advantages have been described in detail, it should be understood that various changes, substitutions and modifications can be made herein without departing from the scope of protection of the patent application.

Claims

1. An inductor material, characterized in that: The invention comprises 96.5-98.6wt% of a composite material and 1.4-3.5wt% of a resin; the composite material comprises 50-80wt% of an insulation-coated coarse powder, 19.9-49.2wt% of an insulation-coated fine powder and 0.1-0.8wt% of a coupling agent, wherein the insulation-coated coarse powder comprises a first magnetic material and a first inorganic coating layer coating the first magnetic material, the surface morphology of the insulation-coated coarse powder is spherical, and the sphericity thereof is 0.75-0.90, the insulation-coated fine powder comprises a second magnetic material and a second inorganic coating layer coating the second magnetic material, the surface morphology of the insulation-coated fine powder is an irregular spherical shape, and the sphericity thereof is 0.05-0.

3.

2. The inductive material according to claim 1, characterized in that: The particle size of the inductor material is distributed in the range of 40 to 120 μm.

3. The inductive material according to claim 1, characterized in that: The coupling agent is an amine compound.

4. The inductive material according to claim 3, characterized in that: The coupling agent is at least one of aminopropylmethyldiethoxysilane, aminopropylmethyltriethoxysilane, aminopropylmethyldimethoxysilane and aminopropylmethyltrimethoxysilane.

5. The inductive material according to claim 1, characterized in that: In the insulating coated coarse powder, the first magnetic material is at least one of amorphous powder, nanocrystalline powder, FeSi powder, FeSiAl powder, FeSiCr powder, and FeNi powder, and the particle size distribution is in the range of 6 to 50 μm. The material of the first inorganic coating layer is at least one of aluminum oxide, silicon oxide, titanium oxide, ZnO, and P2O5, and the thickness of the first inorganic coating layer is 30 to 100 nm; preferably, the first inorganic coating layer has 1 to 3 coating layers; In the insulating coated fine powder, the second magnetic material is at least one of carbonyl iron powder, amorphous powder, FeSi powder, FeSiAl powder, FeSiCr powder, and FeNi powder, and the particle size distribution is in the range of 1 to 12 μm. The material of the second inorganic coating layer is at least one of aluminum oxide, silicon oxide, titanium oxide, ZnO and P2O5, and the thickness of the second inorganic coating layer is 3 to 10 nm; preferably, the second inorganic coating layer has 1-3 coating layers.

6. The inductive material according to claim 1, characterized in that: The resin is at least one of epoxy resin, phenolic resin, acrylic resin and polyimide; preferably, based on the weight of the resin, the resin contains 61-70 wt % of epoxy resin and 30-39 wt % of phenolic resin or polyimide.

7. A method for preparing an inductive material according to any one of claims 1 to 6, characterized in that: The steps include: (1) Preparing insulation-coated coarse powder: performing insulation coating on the first magnetic material to form a first inorganic coating layer to obtain insulation-coated coarse powder; (2) preparing insulation-coated fine powder: performing insulation coating on the second magnetic material to form a second inorganic coating layer to obtain insulation-coated fine powder; (3) Grading: 50-80 wt% of the insulation coated coarse powder, 19.9-49.2 wt% of the insulation coated fine powder and 0.1-0.8 wt% of the coupling agent are diluted into a slurry, and then wet ball milling is performed, spray drying is performed, and grading is performed to obtain a composite material with a particle size of 50-150 μm; (4) Granulation: 96.5-98.6 wt% of the composite material and 1.4-3.5 wt% of the resin are heated and mixed, then cooled and crushed, and the inductor material with a particle size of 40-120 μm is selected.

8. An inductor, characterized in that: The invention comprises a magnet, a coil and a pin, wherein the coil is located in the magnet, the pin is connected to the coil and protrudes from the magnet, and the magnet comprises the inductance material according to any one of claims 1 to 6.

9. The inductor according to claim 8, characterized in that The magnet is formed by pressing the inductive material, and after pressing, the particle size of the surface particles of the magnet is in the range of 20 to 140 μm.

10. The inductor according to claim 8, characterized in that The pin protrudes from the magnet by 0.02 to 0.20 mm.